2016
DOI: 10.1038/srep24231
|View full text |Cite
|
Sign up to set email alerts
|

Detection of colorectal dysplasia using fluorescently labelled lectins

Abstract: Colorectal cancer screening using conventional colonoscopy lacks molecular information and can miss dysplastic lesions. We tested here the ability of fluorescently labelled lectins to distinguish dysplasia from normal tissue when sprayed on to the luminal surface epithelium of freshly resected colon tissue from the Apcmin mouse and when applied to fixed human colorectal tissue sections. Wheat germ agglutinin (WGA) showed significantly decreased binding to adenomas in the mouse tissue and in sections of human c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…Vertical distribution of the ICG fluorescence, localized only at the colon tumor surface, was also observed (Figure 3B ). Fluorescence signal of wheat germ agglutinin (WGA), which binds to glycoproteins and is used for mucus imaging [ 35 ], was observed both in the tumor tissues and normal colonic mucosa (Figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…Vertical distribution of the ICG fluorescence, localized only at the colon tumor surface, was also observed (Figure 3B ). Fluorescence signal of wheat germ agglutinin (WGA), which binds to glycoproteins and is used for mucus imaging [ 35 ], was observed both in the tumor tissues and normal colonic mucosa (Figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the presence of physiological mucus production in the monolayer, live-cell staining with Wheat Germ Agglutinin (WGA) was performed [17,25,26]. We found that the WGA-positive signals were detected across the entire monolayer, suggesting that the epithelial apical surface was covered by mucus-like molecules such as N-acetyl-D-glucosamine ( Fig 4A).…”
Section: Plos Onementioning
confidence: 99%
“…Lectins are glycoproteins that bind to specific sugar residues (oligosaccharides) and have been developed to detect cell-surface glycans that are altered in cancer [ 90 , 109 ]. Unlike other posttranslational modifications, glycosylation is highly specific in cancer and provides a promising biomarker for early cancer detection [ 110 , 111 ].…”
Section: Targeted Optical Imaging Agentsmentioning
confidence: 99%
“…WGA labeled with Alexa Fluor 647 (AF647, λ ex = 650 nm λ em = 668 nm) showed significantly decreased binding in sections of human colonic adenomas ex vivo ( Figure 8(a) ) [ 90 ]. This targeted contrast agent could distinguish among normal epithelium, hyperplastic polyps, low-grade dysplasia, high-grade dysplasia, and adenocarcinoma with high sensitivity, specificity, and positive predictive value (Figures 8(b) and 8(c) ).…”
Section: Targeted Optical Imaging Agentsmentioning
confidence: 99%
See 1 more Smart Citation